Neural conditional ablation of the protein tyrosine phosphatase receptor Delta PTPRD impairs gliogenesis in the developing mouse brain cortex - Cornejo, Francisca; Franchini, Nayhara; Cortés, Bastián I.; Elgueta, Daniela; Cancino, Gonzalo I. (Frontiers in Cell and Developmental Biology, 2024)
Neurodevelopmental disorders are characterized by alterations in the development of the cerebral cortex, including aberrant changes in the number and function of neural cells. Although neurogenesis is one of the most studied cellular processes in these pathologies, little evidence is known about glial development. Genetic association studies have identified several genes associated with neurodevelopmental disorders. Indeed, variations in the PTPRD gene have been associated with numerous brain disorders, including autism spectrum disorder, restless leg syndrome, and schizophrenia. We previously demonstrated that constitutive loss of PTPRD expression induces significant alterations in cortical neurogenesis, promoting an increase in intermediate progenitors and neurons in mice. However, its role in gliogenesis has not been evaluated. To assess this, we developed a conditional knockout mouse model lacking PTPRD expression in telencephalon cells. Here, we found that the lack of PTPRD in the mouse cortex reduces glial precursors, astrocytes, and oligodendrocytes. According to our results, this decrease in gliogenesis resulted from a reduced number of radial glia cells at gliogenesis onset and a lower gliogenic potential in cortical neural precursors due to less activation of the JAK/STAT pathway and reduced expression of gliogenic genes. Our study shows PTPRD as a regulator of the glial/neuronal balance during cortical neurodevelopment and highlights the importance of studying glial development to understand the etiology of neurodevelopmental diseases.